Negotiating Care, Distance, and Well-Being: Psychosocial Dynamics of Transnational Families of Indonesian Migrant Workers - Kalamika, Arin Mamlakah; Umam, Khotibul; Ramdani, Idan; Kurniawati, Pratiwi; Shofi, Rubangi (Da'wa Faculty UIN Saizu Purwokerto, 2026)
This study explores how care, distance, and psychosocial well-being are negotiated within transnational families of Indonesian migrant workers. While migration has long been recognized as a strategy for improving household economic conditions, less attention has been given to the relational and psychosocial consequences of family separation. Addressing this gap, the study employs a qualitative case study approach in Cilacap Regency, one of Indonesia’s major migrant-sending regions. Data were collected through in-depth interviews, participatory observation, and document analysis involving migrant workers and their family members, including spouses, children, and grandparents. The findings reveal that ongoing processes of care negotiation shape transnational family life under conditions of distance and constraint. Communication serves as the primary medium of care but is limited by technological barriers, time differences, and work demands, resulting in only partial emotional connection. Family roles are continuously reconfigured, with men negotiating domestic responsibilities and women maintaining caregiving authority from afar. Grandparents emerge as key caregivers, although intergenerational arrangements often create gaps in emotional care. These dynamics contribute to psychosocial strain, particularly among children and caregivers. This study highlights that family well-being in migration contexts is inherently relational and negotiated, underscoring the need for integrated social work interventions that address psychosocial support, digital inclusion, and gendered care dynamics. Keywords: Transnational families; Psychosocial well-being; Care negotiation; Migration; Social work Penelitian ini mengkaji bagaimana praktik pengasuhan, keterpisahan geografis, dan kesejahteraan psikososial dinegosiasikan dalam keluarga pekerja migran Indonesia. Selama ini, migrasi lebih banyak dipahami sebagai strategi peningkatan kesejahteraan ekonomi, sementara dampak relasional dan psikososial akibat keterpisahan keluarga masih kurang mendapat perhatian. Untuk mengisi kesenjangan tersebut, penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus di Kabupaten Cilacap sebagai salah satu daerah pengirim pekerja migran terbesar di Indonesia. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen yang melibatkan pekerja migran serta anggota keluarga yang ditinggalkan, termasuk pasangan, anak, dan kakek-nenek. Hasil penelitian menunjukkan bahwa kehidupan keluarga transnasional dibentuk oleh proses negosiasi pengasuhan yang berlangsung dalam kondisi keterbatasan dan jarak. Komunikasi menjadi medium utama dalam praktik pengasuhan, namun dibatasi oleh hambatan teknologi, perbedaan waktu, dan tuntutan kerja sehingga menghasilkan kedekatan emosional yang parsial. Peran keluarga mengalami rekonfigurasi, di mana laki-laki menegosiasikan peran domestik, sementara perempuan tetap menjalankan otoritas pengasuhan dari jarak jauh. Kakek-nenek berperan sebagai pengasuh utama, meskipun seringkali muncul kesenjangan dalam pemenuhan kebutuhan emosional anak. Dinamika ini berdampak pada tekanan psikososial, terutama pada anak dan anggota keluarga lainnya. Kata kunci: Keluarga transnasional; Kesejahteraan psikososial; Negosiasi pengasuhan; Migrasi; Pekerjaan sosial